Quality of student psychological counseling service at Vietnam National University, Ho Chi Minh City - Nguyễn Thị Hoàng Mai; Lê Thị Lan Anh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Khoa học Xã hội, 2024)
This study attempts to identify quality attributes and investigate the quality of student psychological counseling service at Vietnam National University, Ho Chi Minh City (VNU-HCM) from the perspective of students, thereby proposing recommendations to improve the service quality in the context that the mental health of students is at an alarming level. Based on the results of desk research in-depth interviews with 09 experts, the study identifies 06 groups of quality attributes: Reliability, Responsiveness, Assurance, Empathy, Tangibles, and Digital technology. Through a survey of 174 students of VNU-HCM who have used student psychological counseling services, the Kano model analysis results classify 28 quality attributes, including 08 must-be attributes, 14 one-dimensional attributes, 02 attractive attributes, and 04 indifferent attributes. In addition, the IPA results indicate 11 attributes that must be maintained, 07 attributes that must be concentrated on, 02 attributes that must be restricted in development, and 08 attributes that must be reduced in the investment. Based on these results, discussions and implications are provided.